Short-interval intracortical inhibition is not affected by varying visual feedback in an isometric task in biceps brachii muscle - Rantalainen, Timo; Weier, Ashleigh; Leung, Michael; Brandner, Chris; Spittle, Michael; Kidgell, Dawson (Frontiers in Human Neuroscience, 2013)
Short-interval intracortical inhibition (SICI) of the primary motor cortex (M1) appears to play a significant role in skill acquisition. Consequently, it is of interest to find out which factors cause modulation of SICI. Purpose: To establish if visual feedback and force requirements influence SICI. Methods: SICI was assessed from 10 healthy adults (5 males and 5 females aged between 21 and 35 years) in three submaximal isometric elbow flexion torque levels (5%, 20% and 40% of maximal voluntary contraction [MVC]) and with two tasks differing in terms of visual feedback. Single-pulse and paired-pulse motor evoked potentials (MEPs), supramaximal M-wave and background surface electromyogram (sEMG) were recorded from the biceps brachii muscle. Results: Repeated measures MANOVA was used for statistical analyses. Background sEMG did not differ between tasks (F = 0.4, P = 0.68) nor was task × torque level interaction observed (F = 1.2, P = 0.32), whereas background sEMG increased with increasing torque levels (P = 0.001). SICI did not differ between tasks (F = 0.9, P = 0.43) and no task × torque level interaction was observed (F = 2.3, P = 0.08). However, less SICI was observed at 40% MVC compared to the 5% and 20% MVC torque levels (P = 0.01 to 0.001). Conclusion: SICI was not altered by performing the same task with differing visual feedback. However, SICI decreased with increasing submaximal torque providing further evidence that SICI is one mechanism of modulating cortical excitability and plays a role in force gradation.